Rapid evaluation of heterologous chimeric RBD-dimer mRNA vaccine for currently-epidemic Omicron sub-variants as booster shot after inactivated vaccine - Qian Chen; Pei Du; Yuxuan Han; Xuehui Ma; Rong Zhang; Xiaoyu Rong; Xu Zhao; Renyi Ma; Huiting Yang; Anqi Zheng; Qingrui Huang; Jinghua Yan; et al. (Elsevier, 2023)
With continuous mutations of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the severe immune escape of Omicron sub-variants urges the development of next-generation broad-spectrum vaccines, especially as booster jabs after high-level vaccination coverage of inactivated vaccines in China and many other countries. Previously, we developed a coronavirus disease 2019 (COVID-19) protein subunit vaccine ZF2001® based on the tandem homo-prototype receptor-binding domain (RBD)-dimer of the SARS-CoV-2 spike protein. We upgraded the antigen into a hetero-chimeric prototype (PT)-Beta or Delta-BA.1 RBD-dimer to broaden the cross-protection efficacy and prove its efficiency with protein subunit and mRNA vaccine platforms. Herein, we further explored the hetero-chimeric RBD-dimer mRNA vaccines and evaluated their broad-spectrum activities as booster jabs following two doses of inactivated vaccine (IV) in mice. Our data demonstrated that the chimeric vaccines significantly boosted neutralizing antibody levels and specific T-cell responses against the variants, and PT-Beta was superior to Delta-BA.1 RBD as a booster in mice, shedding light on the antigen design for the next-generation COVID-19 vaccines.